2020
DOI: 10.1007/s41996-020-00063-0
|View full text |Cite
|
Sign up to set email alerts
|

Foundation Giving and Economics Research Productivity at HBCUs: Empirical Evidence from the Koch Foundation

Abstract: Existing research on funding disparities between historically black colleges and universities (HBCUs) and non-HBCUs primarily focuses on government funding and pays little attention to foundation giving. This paper helps to fill this gap by examining the effects of funding by the Charles Koch Foundation-a major funder of economics research in the USA-on the economics research productivity at HBCUs. Using data from the foundation's tax forms, the Integrated Postsecondary Education Data System (IPEDS), and Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Existing studies have demonstrated the historical exclusion from the research enterprise and significant funding differences for HBCUs compared with PWIs. 37,38 The recognition of this disparity has led to attempts by several programs to affect funding distribution and research productivity (eg, Path to Excellence and Innovation [PEI]). The PEI program specifically targets HBCUs to increase NIH funding from <1% to ≥2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have demonstrated the historical exclusion from the research enterprise and significant funding differences for HBCUs compared with PWIs. 37,38 The recognition of this disparity has led to attempts by several programs to affect funding distribution and research productivity (eg, Path to Excellence and Innovation [PEI]). The PEI program specifically targets HBCUs to increase NIH funding from <1% to ≥2.…”
Section: Discussionmentioning
confidence: 99%
“…The most striking disparity is that all three HBCU medical schools were in the no growth category defined by our study. Existing studies have demonstrated the historical exclusion from the research enterprise and significant funding differences for HBCUs compared with PWIs 37,38 . The recognition of this disparity has led to attempts by several programs to affect funding distribution and research productivity (eg, Path to Excellence and Innovation [PEI]).…”
Section: Discussionmentioning
confidence: 99%